The Effect of Work Motivation, Work Culture, Leadership and Work Experience on Employee Performance at Nusa Tenggara Barat Province, Indonesia - Evania Julpiana; Helmy Fuadi; Tuti Handayani; Dinesh Kumar Manickam; Itır Ceren Morcote Santos; Victory Ikpe (International Journal of Management Science, 2024)
Employee performance is a vital aspect of organizational success, which is influenced by various factors including work motivation, work culture, leadership, and work experience. This study aims to evaluate the influence of these factors on employee performance at BPS Nusa Tenggara Barat (NTB) Province. The research method used is the Chi-Square test to analyze data obtained from a survey conducted on employees of BPS NTB Province. A total of 43 respondents were taken as samples for this study. Data analysis shows that work motivation and work culture have no significant influence on employee performance at BPS NTB Province. However, leadership is proven to have a significant influence on employee performance, while work experience has no significant influence. These findings highlight the importance of management focus on developing effective leadership to improve employee performance at BPS NTB Province.